Distribution and genetic lineages of the Craspedacusta sowerbii species complex (Cnidaria, Olindiidae) in Italy - Morpurgo, Massimo; Marrone, Federico; Ciutti, Francesca; Cappelletti, Cristina; Vorhauser, Samuel; Alber, Renate; Dossena, Matteo; Salmaso, Nico; Fontaneto, Diego; Caputo, Luciano; Vecchioni, Luca (Biology, 2024)
Olindiid freshwater jellyfishes of the genus Craspedacusta Lankester, 1880 are native to eastern Asia; however, some species within the genus have been introduced worldwide and are nowadays present in all continents except Antarctica. To date, there is no consensus regarding the taxonomy within the genus Craspedacusta due to the morphological plasticity of the medusa stages. The species Craspedacusta sowerbii Lankester, 1880 was first recorded in Italy in 1946, and until 2017, sightings of the jellyfish Craspedacusta were reported for 40 water bodies. Here, we shed new light on the presence of the freshwater jellyfishes belonging to the genus Craspedacusta across the Italian peninsula, Sardinia, and Sicily. First, we report 21 new observations of this non-native taxon, of which eighteen refer to medusae sightings, two to environmental DNA sequencing, and one to the finding of polyps. Then, we investigate the molecular diversity of collected Craspedacusta specimens, using a Bayesian analysis of sequences of the mitochondrial gene encoding for Cytochrome c Oxidase Subunit I (mtDNA COI). Our molecular analysis shows the presence of two distinctive genetic lineages: (i) a group that comprises sequences obtained from populations ranging from central to northern Italy; (ii) a group that comprises three populations from northern Italy—i.e., those from the Lake Levico, the Lake Santo of Monte Terlago, and the Lake Endine—and the single known Sicilian population. We also report for the first time a mtDNA COI sequence obtained from a Craspedacusta medusa collected in Spain